2018
DOI: 10.3390/f9090562
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Root Responses of Populus tomentosa Forests to Stand Density

Abstract: Stand density directly affects the distribution of ecological factors such as light, heat, and water in forest communities and changes the diversity and structure of undergrowth species, thereby affecting soil health. Fine roots can provide water and nutrients to plants rapidly in the fierce competition of soil resources, so as to get rid of environmental factors. This study examined the fine-root responses of the Populus tomentosa clone S86 to three stand densities (plant × row spacing: 2 × 2 m, 4 × 3 m, 4 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…Tree root systems are vitally important for the proper functioning of forest ecosystems because of their pivotal roles in the absorption of soil nutrients and water, soil organic matter stock, and for maintaining plant growth, tree stability and stem straightness (Lindström and Rune 1999;Collins and Bras 2007;Xi et al 2011;Pransiska et al 2016;Bo et al 2018;Wang and Xie 2018). Fine roots (diameter < 2 mm) are the most active segments of root systems and respond rapidly to variations in the soil environment (Hendrick and Pregitzer 1992;Lukac and Godbold 2010;Montagnoli et al 2012;Jha 2018;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree root systems are vitally important for the proper functioning of forest ecosystems because of their pivotal roles in the absorption of soil nutrients and water, soil organic matter stock, and for maintaining plant growth, tree stability and stem straightness (Lindström and Rune 1999;Collins and Bras 2007;Xi et al 2011;Pransiska et al 2016;Bo et al 2018;Wang and Xie 2018). Fine roots (diameter < 2 mm) are the most active segments of root systems and respond rapidly to variations in the soil environment (Hendrick and Pregitzer 1992;Lukac and Godbold 2010;Montagnoli et al 2012;Jha 2018;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization is one of the most important practices to maintain tree growth and rubber yield because root morphology depends significantly on nutrient availability (Fransen et al 1998). Trees increase their number of fine roots to absorb more soil nutrients (Bo et al 2018). Normally, rubber planters are encouraged to apply chemical fertilizer and organic materials to an excavated fertilization cave (typically 100-200 cm long × 60 cm wide × 40 cm deep) between rows by taking advantage of the physiological plasticity of roots to obtain nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Stand density influences soil environments by affecting the availability of nutrients (Bo et al 2018), and is regarded as In black locust plantations, soil C and N contents showed a cumulative trend in low stand densities, peaked at density class III, then decreased slightly with increasing density. Organic C and N content were closely related on a small scale to stand density (Chen 2006).…”
Section: Changes In Soil and Leaf Traits Along The Stand Density Gradientmentioning
confidence: 99%
“…In forest plantations, stand density is a major index representing resource use conditions and interactions among and between trees and environments; thus, it is of major consideration in management practices. Stand density determines stand spatial structure and directly affects the distribution of light, heat, moisture, and other ecological factors affecting the growth of individual trees and of the plantation (Cai et al 2016;Hakkenberg et al 2016;Bo et al 2018). The effect of stand density on fine root dynamics has been studied in natural forests coupled with species richness (He et al 2005;Marquard et al 2009;Zeng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Higher soil P was related to higher fine root P concentration in P . tomentosa plantations, but inconsistent trends where observed for fine root N and potassium (K) 51 . Yet, N-fertilization led to a 3-fold increase in fine root N concentrations in P .…”
Section: Introductionmentioning
confidence: 99%